TRINGO TAMANSISWA (NGERTI, NGRASA, NGLAKONI): THE DEVELOPMENT OF SUBJECT SPECIFIC PEDAGOGY WITH VALUE CLARIFICATION-INQUIRY LEARNING - Astuti Wijayanti; Asri Widowati (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2019)
Inquiry learning based on clarifying values is one of the innovative education that cannot separate from the reality of daily life, which involves students actively and internalizing values in students. This study aims to describe the development of subject-specific pedagogy with value clarification-based learning to develop tringo. Through this learning, students are invited to understand, experience, and manage so that learning becomes more meaningful. Teachers should prioritize not only cognitively but also psychomotor and affective. So, the value of the investment is carried out in an integrated and consistent manner in science learning to form a generation that is not only smart but also personality or character. The research method used is the modification of the RD model of Plomp and Ely, namely: 1) formulating needs; 2) designing; 3) data preparation; 4) preparation and writing; 5) integration and evaluation; 6) making the initial master; and 7) master. Data collection techniques were carried out using observation techniques, interview techniques, documentation techniques, and questionnaire techniques. The results of this study are the development of the concept of 'tringo' which internalized through a value clarification approach. And developing an attitude of tolerance, the emergence of self-discipline, having a sense of responsibility, developing a work ethic, having a sense of openness, being able to think positively, developing self-potential, cooperating, respect each other and foster honesty. value clarification learning can use as one of the innovation models in meaningful learning.